2019
DOI: 10.26754/ojs_ried/ijds.364
|View full text |Cite
|
Sign up to set email alerts
|

La inclusión de las personas con discapacidad en los acuerdos de paz de Colombia

Abstract: Existe una especial conexión entre discapacidad y conflicto armado. Las situaciones graves de violencia no solo generan nuevas discapacidades, sino que agravan las existentes. Teniendo en cuenta que la discapacidad es una cuestión de derechos humanos, así como el alto número de víctimas del conflicto que tienen algún tipo de discapacidad, hubiese sido deseable que el Acuerdo Final de Paz con las FARC-EP en Colombia incluyese un enfoque específico sobre discapacidad. Su ausencia puede contribuir a perpetuar su … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Finally, preliminary reports have stated that there are FARC with significant psychological and mental health needs from the conflict [ 11 ]. Though widespread data on diagnosis frequency and burden of mental health conditions for FARC ex-combatants are not yet available, studies conducted with other demobilized armed groups in Colombia have demonstrated rates of PTSD above 50% [ 30 ]. Future studies could focus on comparing specific healthcare needs among these vulnerable subpopulations of FARC ex-combatants or differentiating healthcare access barriers and effective interventions for addressing them among these groups.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, preliminary reports have stated that there are FARC with significant psychological and mental health needs from the conflict [ 11 ]. Though widespread data on diagnosis frequency and burden of mental health conditions for FARC ex-combatants are not yet available, studies conducted with other demobilized armed groups in Colombia have demonstrated rates of PTSD above 50% [ 30 ]. Future studies could focus on comparing specific healthcare needs among these vulnerable subpopulations of FARC ex-combatants or differentiating healthcare access barriers and effective interventions for addressing them among these groups.…”
Section: Discussionmentioning
confidence: 99%